A Study On Spray Characteristics Of Straight Vegetable Oil - Abdul Adam, Abdullah (2010)

(untitled)
Biodiesel is considered a promising alternative fuel to reduce the dependent on fossil fuel without any major modification on existing engines system. Compared to diesel fuel, biodiesel has several superior combustion characteristics. It has the advantages of high biodegradability, excellent lubricity and no sulfur content. For example, when biodiesel is used inside the engine, approximately 10wt% of its oxygen content promote more complete combustion process and effectively reduce unburned hydrocarbons (UHC), carbon monoxide (CO) as well as suspended aerosol carbon granules. Although biodiesel has many advantages on the fuel properties, the fuel consumption rate or lower horsepower output are still need to be improved. This is due to the differences in fuel properties especially the kinematic viscosity between diesel fuel (GO), biodiesel fuel (BDF) and straight vegetable oil (SVO). In this study, the effect of kinematic viscosity of SVO on fuel injection spray characteristicare investigated using constant volume high pressure spray chamber.